Study of Preference for Surround Microphone Techniques Used in the Recording of Choir and Instrumental Ensemble - SITEK, Andrzej; KOSTEK, Bożena (Archives of Acoustics, 2013)
The aim of this paper is to describe the process of choosing the best surroundmicrophone technique for recording of choir with an instrumental ensemble. First,examples of multichannel microphone techniques including those used in the recordingare described. Then, the assumptions and details of music recording in RadioGdansk Studio are provided as well as the process of mixing of the multichannelrecording. The extensive subjective tests were performed employing a group of soundengineers and students in order to find the most preferable recording techniques. Becausethe final recording is based on the mix of “direct/ambient” and “direct-soundall-around” approaches, a subjective quality evaluation was conducted and on thisbasis the best rated multichannel techniques were chosen. The results show thatlisteners might consider different factors when choosing the best rated multichanneltechniques in separate tasks, as different systems were chosen in the two tests.